A Successful Application of Phosphazene Base P2‐tBu to [11C]ABP688 Radiosynthesis in Fully Automated Synthesis Module. (16th August 2020) - Lee, Jihye
Abstract : [ 11 C]ABP688 is the radioligand widely used for metabotropic glutamate subtype 5 (mGluR5) imaging in positron emission tomography (PET). The successful production of [ 11 C]ABP688 in commercial automated synthesis module with hindered strong organic base was achieved. I compared 1, 8‐bis(tetramethylguanidino)naphthalene (TMGN), tert‐butylimino‐tri(pyrrolidino)phosphorane (BTPP), P2‐tBu, P4‐tBu, and NaH as a base for C‐11 methylation of oxime and found P2‐tBu would be a suitable alternative for the conventional inorganic bases (NaH or NaOH). Considering the GMP application, P2‐tBu can provide compatibility with automated synthesizer and the resulting reliable synthesis. Three batches of the optimized condition for [ 11 C]ABP688 synthesis were examined for quality assurance. Abstract : Radiosynthesis of [11C]ABP688 under the optimized condition (P2‐tBu, 1.5 eq)